Neural mechanisms of early-life social stress as a developmental risk factor for severe psychiatric disorders - Reinwald, Jonathan Rochus; Becker, Robert; Mallien, Anne Stephanie; Falfán‐Melgoza, Claudia; Sack, Markus; Clemm von Hohenberg, Christian; Braun, Urs; Cosa‐Linan, Alejandro; Gass, Natalia; Vasilescu, Andrei-Nicolae; Tollens, Fabian; Lebhardt, Philipp; et al. (Biological psychiatry, 2017)
Background To explore the domain-general risk factor of early-life social stress in mental illness, rearing rodents in persistent postweaning social isolation has been established as a widely used animal model with translational relevance for neurodevelopmental psychiatric disorders such as schizophrenia. Although changes in resting-state brain connectivity are a transdiagnostic key finding in neurodevelopmental diseases, a characterization of imaging correlates elicited by early-life social stress is lacking. Methods We performed resting-state functional magnetic resonance imaging of postweaning social isolation rats (N = 23) 9 weeks after isolation. Addressing well-established transdiagnostic connectivity changes of psychiatric disorders, we focused on altered frontal and posterior connectivity using a seed-based approach. Then, we examined changes in regional network architecture and global topology using graph theoretical analysis. Results Seed-based analyses demonstrated reduced functional connectivity in frontal brain regions and increased functional connectivity in posterior brain regions of postweaning social isolation rats. Graph analyses revealed a shift of the regional architecture, characterized by loss of dominance of frontal regions and emergence of nonfrontal regions, correlating to our behavioral results, and a reduced modularity in isolation-reared rats. Conclusions Our result of functional connectivity alterations in the frontal brain supports previous investigations postulating social neural circuits, including prefrontal brain regions, as key pathways for risk for mental disorders arising through social stressors. We extend this knowledge by demonstrating more widespread changes of brain network organization elicited by early-life social stress, namely a shift of hubness and dysmodularity. Our results highly resemble core alterations in neurodevelopmental psychiatric disorders such as schizophrenia, autism, and attention-deficit/hyperactivity disorder in humans.
Gesehen am 09.05.2018